2006
DOI: 10.1089/thy.2006.16.757
|View full text |Cite
|
Sign up to set email alerts
|

The Trapping-Only Nodules of the Thyroid Gland: Prevalence Study

Abstract: The aim of this study was to determine the prevalence of trapping-only nodules of the thyroid gland. The study was prospectively performed in patients bearing hot or warm thyroid nodules at pertechnetate scan in the presence of circulating thyrotropin (TSH) within the normal range. The study was restricted to these patients because nodules that suppress TSH are certainly autonomous. In 140 patients showing hot or warm nodules at 30-minute pertechnetate scintigraphy, and normal TSH levels, radioiodine scintigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 19 publications
(23 reference statements)
0
30
0
2
Order By: Relevance
“…This discordance is observed in only 5% of patients and therefore could not explain our results (24). In the same way, thyroid hormone suppression tests were not done; therefore, we cannot exclude the possibility that some nodules with increased 99m technetium uptake are not autonomously functioning.…”
Section: Tco4mentioning
confidence: 73%
“…This discordance is observed in only 5% of patients and therefore could not explain our results (24). In the same way, thyroid hormone suppression tests were not done; therefore, we cannot exclude the possibility that some nodules with increased 99m technetium uptake are not autonomously functioning.…”
Section: Tco4mentioning
confidence: 73%
“…The full text of six eligible articles was retrieved and two additional studies were found screening the references of the selected articles. Finally, eight articles including series of patients with AFTN were selected for the meta-analysis [16,[21][22][23][24][25][26][27] (Fig. 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…studies [22,24] were found, while the remaining studies were retrospective and monocentric. Concerning the geographic distribution, studies from Europe, Asia and America were included.…”
Section: Qualitative and Quantitative Analysis (Meta-analysis)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SNM guidelines list the advantages and disadvantages of 99m Tc-pertechnetate and 123 I-iodide for thyroid imaging (Table 3) (2). In addition to those items (Table 3), many publications have reported discordant results for thyroid nodules when imaged with these 2 different agents (8)(9)(10)(11). Cold thyroid nodules seen on a 123 I scan sometimes appear to accumulate 99m Tc-pertechnetate.…”
Section: Discussionmentioning
confidence: 99%